(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe disease patterns and analyze the association between dialysis duration, age, and hematological–biochemical indices in chronic hemodialysis patients. Methods: A cross-sectional study was conducted on 125 patients at Transport Hospital (2023–2024). Clinical, hematological, and biochemical data were compared between patients with <5 vs. >5 years of dialysis, and multivariate regression was performed with age and dialysis duration. Results: Hypertension surpassed glomerulonephritis as the leading cause of end-stage renal disease. Patients with shorter dialysis duration had more comorbidities (hypertension 68.3%, diabetes 23.8%). Longer dialysis duration correlated positively with reticulocyte ratio (Coef = 0.03; p<0.001), reticulocyte hemoglobin content (Coef = 0.08; p<0.01), and ferritin (Coef = 28.74; p<0.001). Older age correlated inversely with urea, creatinine, Na⁺, K⁺, and albumin (p<0.05). Conclusions: The disease spectrum among hemodialysis patients is shifting, with rising prevalence of hypertension and comorbidities. Personalized management strategies should be tailored according to age and hematologic–biochemical indices.